1968
DOI: 10.1192/bjp.114.508.345
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gilles de la Tourette's Syndrome with Haloperidol

Abstract: Gilles de la Tourette's syndrome is an unusual condition with undetermined aetiology, treatment, and prognosis (1, 2, 3). Less than 50 case studies have been reported in the literature. This paper will present a detailed report of a case treated for 18 months, and brief summaries of two cases treated for three weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(44 citation statements)
references
References 15 publications
1
42
0
1
Order By: Relevance
“…However, significant side effects, including extrapyramidal symptoms (EPS) such as acute dystonic reactions, Parkinsonism, akathisia, and tardive dyskinesia (Shapiro et al 1973), have led to use of the newer atypical neuroleptics. In recent years, the atypical neuroleptics have been used frequently to treat tics in youth with TD; however, reports have emerged demonstrating serious adverse effects, including substantial weight gain, development of abnormal glucose and lipid metabolism, elevated serum prolactin levels, and=or cardiac effects such as prolongation of the QTc interval (Green 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, significant side effects, including extrapyramidal symptoms (EPS) such as acute dystonic reactions, Parkinsonism, akathisia, and tardive dyskinesia (Shapiro et al 1973), have led to use of the newer atypical neuroleptics. In recent years, the atypical neuroleptics have been used frequently to treat tics in youth with TD; however, reports have emerged demonstrating serious adverse effects, including substantial weight gain, development of abnormal glucose and lipid metabolism, elevated serum prolactin levels, and=or cardiac effects such as prolongation of the QTc interval (Green 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The re sponse of both motor and vocal tics to typical neurolep tic agents (Seignot 1961;Shapiro et al 1973) and the demonstration of altered levels of homovanillic acid (HV A) in the cerebrospinal fluid (CSF) of some patients (Cohen et al 1979;Singer et al 1982) have suggested a primary role for the dopamine system in TS, perhaps involving increased sensitivity of dopamine receptors or postsynaptic mechanisms to which these receptors are coupled. However, models derived from pharmaco logic information in this fashion inevitably suffer from a lack of anatomic specifIcity.…”
mentioning
confidence: 99%
“…Multiple clinicians (Seignot 1961;Challas and Brauer 1963;Chapel et al 1964;Abuzzahab and Anderson 1973;Shapiro et al 1973) reported the efficacy of haloperidol (HAL) in the treatment of tics and TD (Table 1). HAL was approved by the FDA for the treatment of adult TD patients in 1969 and for children in 1978.…”
Section: Classic or Typical Antipsychoticsmentioning
confidence: 99%